Emotional Dynamics and Potential Burnout of Indonesian Digital Native EFL Teachers amid Uncertainty in Curriculum Change - Fatiha, Nabila Rosnanda Amelia; Amin, Muhammad; Thohir , Lalu (Journal of Educational Sciences, 2026)
This study investigates the emotional dynamics and potential burnout of Indonesian Digital Native EFL teachers amid uncertainty in curriculum change. The research aimed to examine teachers’ emotional responses, the impact on professional performance, and the relationship between curriculum uncertainty and burnout. This study employed an embedded mixed methods design involving 48 Digital Native EFL teachers from West Nusa Tenggara. Data were collected through Likert-scale questionnaires and open-ended responses and analysed using descriptive statistics, thematic analysis, and Spearman correlation. The findings revealed that teachers experienced both positive and negative emotions, with hope and optimism emerging as dominant responses, while anxiety and frustration were reported at moderate levels. Curriculum uncertainty affected lesson planning, teaching clarity, and motivation. The correlation analysis indicated a strong positive relationship between curriculum uncertainty and teacher burnout. Qualitative findings further revealed coping strategies such as peer collaboration and professional development, alongside stress caused by unclear curriculum direction. The study concludes that curriculum uncertainty influences teachers’ emotional wellbeing and professional performance. Institutional support and clear guidance are essential to reduce burnout risk and maintain instructional effectiveness.